The Relevance of K.H. Ahmad Dahlan's Tajdid Thoughts on Islamic Education During the Covid-19 Pandemic - Mohammad Jailani; Suyadi Suyadi (Jurnal Educative: Journal of Educational Studies, 2021)
The purpose of this study is to examine Tajdid K.H. Ahmad Dahlan’s concept of Islamic education and its relevance during the Covid-19 pandemic. The advancement of science and technology in the modern era, as well as the the emergence of research on the relevance of K.H. Ahmad Dahlan in the development of educational learning in Indonesia, is relevant in the discourse of Islamic education (tajdid). Research data are taken from library references in the form of published research, both manually and digitally, that focus on discussing K.H. Ahmad Dahlan's thoughts in Islamic education. The study’s findings demonstrate that K.H. Ahmad Dahlan’s concept of tajdid is in line with the advancement of Islamic education.Tujuan penelitian ini adalah menganalisis konsep pemikiran Tajdid K.H. Ahmad Dahlan terhadap pendidikan Islam dan relevansinya di masa pandemi Covid-19. Perkembangan ilmu pengetahuan dan teknologi diera modern ini, sejalan dengan munculnya penelitian tentang relevansi pemikiran K.H. Ahmad Dahlan dalam pengembangan pembelajaran pendidikan di Indonesia, dalam perspektif ilmu pendidikan Islam disebut dengan pembaharuan (Tajdid). Data penelitian ini bersumber dari referensi kepustakaan berupa jurnal ilmiah maupun penelusuran terhadap referensi-referensi karya penelitian, baik secara manual maupun digital yang fokus membahas pemikiran K.H. Ahmad Dahlan dalam pendidikan Agama Islam. Hasil penelitian membuktikan bahwa konsep Tajdid K.H. Ahmad Dahlan sesuai dengan pembaharuan dengan peningkatan pendidikan Islam.